2012
DOI: 10.1186/1471-2318-12-42
|View full text |Cite
|
Sign up to set email alerts
|

Respite: carers’ experiences and perceptions of respite at home

Abstract: BackgroundInformal carers play an important role in supporting people with long-term conditions living at home. However, the caring role is known to have adverse effects on carers such as poorer emotional health and social isolation. A variety of types of respite may be offered to carers but little is known about the benefits of respite, carers’ experiences with it, or their perceptions of care workers. This study therefore investigated these experiences and perceptions.MethodRecorded, semi-structured intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
(37 reference statements)
3
24
0
Order By: Relevance
“…The partnership between caregiver, care recipient, and respite provider should be the central component of respite service, although caregiver and care recipient may have different outlooks and benefit in different ways from respite care. The present study found that the caregivers would accept volunteer respite care as long as the dependent person felt or appeared comfortable and agreed to letting another person care for him or her, which has also been reported by other authors (Greenwood et al, 2012; Neville, Beattie, Fielding, & MacAndrew, 2015; Stirling et al, 2014) and highlights the importance of the relationship between all three stakeholders.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The partnership between caregiver, care recipient, and respite provider should be the central component of respite service, although caregiver and care recipient may have different outlooks and benefit in different ways from respite care. The present study found that the caregivers would accept volunteer respite care as long as the dependent person felt or appeared comfortable and agreed to letting another person care for him or her, which has also been reported by other authors (Greenwood et al, 2012; Neville, Beattie, Fielding, & MacAndrew, 2015; Stirling et al, 2014) and highlights the importance of the relationship between all three stakeholders.…”
Section: Discussionsupporting
confidence: 88%
“…Another desirable characteristic of the volunteer, reported by the caregivers, is that they should belong to a volunteer service institution. Similar results were found in the UK, where informal caregivers of elders trusted in the good service provided by paid and voluntary caregivers due to the fact that they were recommended by a government agency (Greenwood et al, 2012). Several studies report that the informal caregiver’s trust is partially based on its trust in the institution that provides the respite service, as well as its trust in the person providing the care.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations